Evaluation of Sabine’s Formula on the prediction and control of reverberant noise in a modern LEED Platinum certified research building - Quinn-Vawter, Christopher, author; Reynolds, Stephen J., advisor; Brazile, William J., committee member; Wilson, Bryan D., committee member (Colorado State University. Libraries, 2016)
The Powerhouse Energy Campus is a LEED Platinum certified research building located in Fort Collins, Colorado and is part of Colorado State University. Completed in 2014, the renovated interior of the Powerhouse consists largely of open floor plans with minimal closed rooms to allow the building's heating and cooling system to function. The open floor plan and use of interior building materials with hard surfaces created problematic noise levels for the office occupants as noise from laboratory spaces or offices could be heard throughout the building. This project provided a unique opportunity to evaluate the method available to most industrial hygienists to measure and predict reverberant noise: Sabine's Formula and the impulse noise method of reverberation measurement. Reverberation times (RT60) in five interior spaces ranging from 76 m3 to 5400 m3 were modeled using a Sabine's Formula model. The RT60 predictions were then compared to the reverberation times measured in each location, and reverberant noise treatments were designed for two rooms using the same models. The RT60 times were taken again after the installation of the recommended treatments for two rooms. This allowed for the evaluation of both the modeling capabilities of Sabine's Formula and the practical industrial hygiene application of the equation to select effective acoustic treatments to control reverberant noise. The model performed well in room volumes 620 m3 and below, and would have likely performed better in the large volume rooms if they did not have such complex, open acoustic environments. The model was still slightly underestimating reverberation times at 620 m3 indicating that it would perform well in larger volume spaces, though this study was not able to identify the room volume at which Sabine's Formula begins to overestimate reverberation times. The RT60 time reductions in both the first floor classroom and the second floor conference room indicated that the reverberant noise treatment design was successful in reducing the problem acoustics in those areas. The treatment reduced the RT60 times at the problematic low frequencies in both rooms and brought the times near the goal of 0.5-1 second. The researchers found that the Sabine's Formula model is able to adequately predict the reverberant field behavior when different acoustic treatments are applied to the space. The impulse noise method of reverberation measurement is also sufficient to characterize the acoustics of a room to aid in the design and selection of acoustic treatments.